The associations of indoor environment and psychosocial factors on the subjective evaluation of Indoor Air Quality among lower secondary school students: a multilevel analysis. (18th April 2016) - Finell, E.; Haverinen‐Shaughnessy, U.; Tolvanen, A.; Laaksonen, S.; Karvonen, S.; Sund, R.; Saaristo, V.; Luopa, P.; Ståhl, T.; Putus, T.; Pekkanen, J.
Abstract: Subjective evaluation of Indoor Air Quality (subjective IAQ) reflects both building‐related and psychosocial factors, but their associations have rarely been studied other than on the individual level in occupational settings and their interactions have not been assessed. Therefore, we studied whether schools' observed indoor air problems and psychosocial factors are associated with subjective IAQ and their potential interactions. The analysis was performed with a nationwide sample ( N  = 195 schools/26946 students) using multilevel modeling. Two datasets were merged: (i) survey data from students, including information on schools' psychosocial environment and subjective IAQ, and (ii) data from school principals, including information on observed indoor air problems. On the student level, school‐related stress, poor teacher–student relationship, and whether the student did not easily receive help from school personnel, were significantly associated with poor subjective IAQ. On the school level, observed indoor air problem (standardized β  = −0.43) and poor teacher–student relationship (standardized β  = −0.22) were significant predictors of poor subjective IAQ. In addition, school‐related stress was associated with poor subjective IAQ, but only in schools without observed indoor air problem (standardized β  = −0.44).